The Use of Metal Threads in the Decoration of Late and Post-Byzantine Embroidered Church Textiles - Anna Karatzani (Cahiers Balkaniques)
Abstract: This paper discusses the result of the technical analysis of metal threads used in the decoration of Byzantine and post Byzantine embroidered church textiles. The study of minute samples from embroidered textiles dated between the 14th and the 19th centuries from Greek Institutions gave information about the types of metal threads as well as the manufacturing techniques and the materials used for their production.Only wires and metal strips wound around a silk core (wound strips) are recorded in the Byzantine‑Greek context from the 14th throughout the 17th century. From then onwards more types such as strips, tir‑tir threads, sequins (as metal decorative elements) and numerous combined threads are introduced, while wires are used less. The use of these new threads is related to the general stylistic changes that occurred in church embroidery during that time through the influence of Western European and Eastern traditions.